2001
DOI: 10.1159/000047374
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Trauma as the Major Cause of Troponin T Release after Transvenous Implantation of Cardioverter/Defibrillators

Abstract: To study the cause of myocardial injury after elective transvenous insertion of a cardioverter/defibrillator, we measured troponin T (TnT) release in 27 patients. Five patients needing only replacement of the generator with threshold testing served as controls. Compared to the control group, a significant increase in TnT occurred in the patients undergoing insertion, which was greatest in the group receiving screw-in electrodes. There was no correlation between TnT and the number and energy of the shocks and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 5 publications
3
13
0
1
Order By: Relevance
“…In accordance with these results, histological data from animal studies have shown that areas of myocardial necrosis were adjacent to the distal electrode through which electric shocks were given 9 . Other investigators have emphasized the role of mechanical injury caused during lead placement as the source of myocardial damage underlying troponin release 7 …”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In accordance with these results, histological data from animal studies have shown that areas of myocardial necrosis were adjacent to the distal electrode through which electric shocks were given 9 . Other investigators have emphasized the role of mechanical injury caused during lead placement as the source of myocardial damage underlying troponin release 7 …”
Section: Introductionmentioning
confidence: 57%
“…It is unknown, however, whether this sequence of events leads to myocardial damage detectable by contemporary clinical means. The evidence for this is indirect and comes mostly from studies of patients undergoing transvenous implantation of an implantable cardioverter defibrillator (ICD), which is invariably followed by cardiac troponin release 5,6,7 . The exact mechanism of myocardial damage in these patients is, however, controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Endocardial lead implantation, whether for antibradycardia pacemakers (304) or transvenous cardioverter-defibrillators (305), typically results in low-level myocardial injury (troponin T and troponin I Ͻ1.5 ng/ml) through mechanical trauma related to the types and diameters of leads used; control patients who only undergo generator replacement have no troponin release. Repeated discharges during internal defibrillator implantation/testing demonstrate troponin elevations in 40% to 90% of patients, although the data conflict as to whether number of shocks and/or delivered energy level correlate with peak levels or percent positive samples among patients (306 -308).…”
Section: Appendix 1 Relevant Author Relationships With Industry and mentioning
confidence: 99%
“…"Catecholamine overload" (ref. [27][28][29] or direct mechanical damage [30][31][32][33][34][35][36][37][38][39] during skiascopy of the heart (during pacemaker implantation) can be a marker of procedure complexity and may positively correlate with troponin levels 31 . Left ventricular failure 40 , right ventricular failure [41][42][43] , or the disparity between physiological degradation of the myocardium and insufficient elimination of its fragments (renal insufficiency) (ref.…”
Section: Methodsmentioning
confidence: 99%
“…However, this study was also relatively small, and individual risk factors related to the studied phenomenon appeared sporadically. In a study by Dworschak 36 , elevated troponin T levels were found after the implantation of defibrillation electrodes in 27 patients. Troponin levels were higher when systems with active fixation were implanted, and the levels did not correlate with test discharge energy.…”
mentioning
confidence: 98%